Comparative study of water quality of Cikapundung river in Citarum Subwatershed - Supriatna, Upi; Rasmilah, Ikeu; Nenih, Neneng (Nashir Al-Kutub Indonesia, 2024)
The Cikapundung River is part of the Citarum Watershed that flows from North Bandung to the South. Cikapundung river water experiences pollution during the irrigation process from upstream to downstream, which is caused by activities in residential areas, markets and industries. Based on this, research is needed to determine the quality of Cikapundung river water with macrobenthos indicators. Macrobenthos is considered a biodicator of water quality because its presence can change according to the level of pollution in the aquatic ecosystem. The research method used is laboratory testing, which compares three locations in the Cikapundung River, namely in Taman Sari (Station one), Kordon Market (Station two) and Citepus (Station 3). The three stations will take water samples for laboratory tests and identify what macrobenthos survive in these waters. The results showed that station one had a Diversity Index of 1.423, Diversity Index of 0.684 and Dominance Index of 0.318, Temperature of 24.90C, Turbidity of 63, TDS of 0087 ppm/3.44333 mg/L, TSS of 375 mg/L, pH of 6.0, DO of 3.0, COD of 174 mg/L, BOD5 of 13.5 mg/L. Station two has a Diversity Index of 1.158, a Diversity Index of 0.557 and a Dominance Index of 0.378, a Temperature of 26.60C, Turbidity of 46.2, TDS of 0199 ppm/2.5345 mg/L, TSS of 39 mg/L, pH of 6.5, DO of 2.9, COD of 251 mg/L, BOD5 of 21 mg/L, Station three has a Diversity Index of 1.216, Diversity Index of 0.104 and Dominance Index of 0.625, Temperature of 310C, Turbidity of 93.8, TDS of 0732 ppm / 1.98777 mg/L, TSS of 3042 mg/L, pH of 7.5, DO of 1.7, COD of 696 mg/L, BOD5 of 37 mg/L. Based on this, it can be concluded that station one is in a lightly polluted position, station two is in a moderately polluted position and station three is in a heavily polluted position.